The use of Adobe Photoshop to create unrealistic female beauty stereotypes: ten media cases and four professional visions in Spain - Bellón Rodríguez, Ana; Rodríguez Rey, Noelia (Comunicación y Género [Communication and Gender], 2021)
An exploratory-descriptive study is carried out about the use of the Adobe Photoshop photo editor for the digital retouching of images of famous women published on the covers of Spanish publications between 2010 and 2018, with which stereotypes of unreal feminine beauty are transferred, as a perfect silhouette a few weeks after giving birth or a face without age-specific wrinkles. Ten cases involving presenters, models, singers, actresses and socialites (Pilar Rubio, Amaia Romero, Mª Teresa Campos, Chenoa, Inma Cuesta, Laura Pausini, Paula Echevarría, Isabel Preysler / Carmen Martínez-Bordiú, are located and analyzed. Miriam Giovanelli and Sara Carbonero) and are published in Hola Fashion, the official magazine of Operación Triunfo, Semana, Interview, Dominical, Yo Dona, Elle, Hola, FHM Spain and Cosmopolitan. Four in-depth interviews are carried out with different profiles (psychologist, actress, graphic editor and photographer) to have a multidisciplinary visión.